2022
DOI: 10.3390/ijerph192417071
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction Goes a Long Way: The Mediating Role of Teaching Satisfaction in the Relationship between Role Stress and Indices of Psychological Well-Being in the Time of COVID-19

Abstract: The COVID-19 pandemic and its containment measures has resulted in drastic changes in the educational landscape. Teachers had to rapidly adapt to shifts in their work-related roles and responsibilities. This situation likely led to role stress and affected the levels of job satisfaction, mental health and general life satisfaction. In this study, we examined the role of teachers’ job satisfaction in the relationship between role stress and indices of psychological well-being. The participants were South Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…11 While the pandemic was involuntary and carried significant difficulties, over the long term, it created novel distance education technologies and pedagogical innovations. 50 Teachers benefitted from flexibility, the possibility of creating new teaching methods, and the opportunity to learn new skills while teaching online. 11 Educators might benefit from adopting a blended approach that combines online and face-to-face learning to overcome the limitations of purely online learning and provide a more effective and engaging learning experience.…”
Section: Discussionmentioning
confidence: 99%
“…11 While the pandemic was involuntary and carried significant difficulties, over the long term, it created novel distance education technologies and pedagogical innovations. 50 Teachers benefitted from flexibility, the possibility of creating new teaching methods, and the opportunity to learn new skills while teaching online. 11 Educators might benefit from adopting a blended approach that combines online and face-to-face learning to overcome the limitations of purely online learning and provide a more effective and engaging learning experience.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study on teacher's professional identity showed that a balance between the three work dimensions (personal-time with family and for leisure; professional-roles and responsibilities; and situational-context of work environment) had a positive influence on their job satisfaction and psychological well-being [70]. A study conducted by Padmanabhanunni and Pretorius [71] showed that teacher's identity was negative correlated with anxiety, hopelessness, role ambiguity, and role stress. In other words, teacher's who had a higher perception of their identity as an educator had levels of ambiguity, anxiety and stress.…”
Section: Investigated Teachermentioning
confidence: 99%
“…This study suggests organizations to provide adequate support and improve employee work control as an effort to reduce job stress. Duan et al, (2022) this study examined the effect of workload and job stress on the performance of medical personnel in the United States. The results showed that workload has a positive effect on job stress, which in turn has a negative effect on employee performance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%